Name:_____________________

Date:______________________
Calc II Sample Key: Chapter 8
1. Use the Trapezoidal Method with 𝑛 = 4 to approximate
∫ 3π‘₯ 𝑑π‘₯. 𝑏
βˆ’ π‘Ž 3 βˆ’ (βˆ’1)
=
=1 𝑛

4 π‘₯
= βˆ’1, π‘₯ = 0, π‘₯ = 1, π‘₯ = 2, π‘₯ = 3 𝑓
(π‘₯ ) = 3π‘₯ ; 𝑏

βˆ’π‘Ž
(𝑓(βˆ’1) + 2𝑓(0) + 2𝑓(1) + 2𝑓(2) + 𝑓(3))
2𝑛
1
= (3 + 2 β‹… 0 + 2 β‹… 3 + 2 β‹… 12 + 27) = 30
2

∫ 3π‘₯ 𝑑π‘₯ β‰ˆ

(The integral actually equals 28, just in case you were curious.)
2. Use Simpson’s method with 𝑛 = 4 to approximate ∫ π‘₯ 𝑑π‘₯ . 𝑏
βˆ’π‘Ž 9βˆ’1
=
=2 𝑛

4 π‘₯
= 1, π‘₯ = 3, π‘₯ = 5, π‘₯ = 7, π‘₯ = 9 𝑓
(π‘₯ ) = π‘₯ ;

∫ π‘₯ 𝑑π‘₯ β‰ˆ 𝑏

βˆ’π‘Ž
(𝑓(1) + 4𝑓(3) + 2𝑓(5) + 4𝑓(7) + 𝑓(9))
3𝑛
2
= (1 + 4 β‹… 27 + 2 β‹… 125 + 4 β‹… 343 + 729) = 1640
3

(The integral actually DOES equal 1640, just in case you were
curious.)

∫ 𝑑π‘₯) √ 𝑑π‘₯ π‘₯+𝐢 𝑒 =π‘₯βˆ’4 𝑑𝑒 = 𝑑π‘₯ =∫ 8(𝑒 + 4) + 7 8𝑒 + 39 𝑑𝑒 = ∫ 𝑑𝑒 = ∫(8𝑒 𝑒 𝑒 = 8 ln |𝑒| βˆ’ 39𝑒 + 39𝑒 + 𝐢 = 8 ln|π‘₯ βˆ’ 4| βˆ’ )𝑑𝑒 39 +𝐢 π‘₯βˆ’4 You can also do this by partial fractions: rewrite the integral as 𝑑π‘₯ + ∫ ( ) 𝑑π‘₯ and solve for 𝐴 and 𝐡. . evaluate the given integral. 3. except numerical integration. ∫ you get 𝐴 = 8 and 𝐡 = 39. (Try it on your own.For the remaining problems.) But I think this 𝑒-substitution is easier. You may use any method discussed in class. ∫ 𝑑π‘₯ = (∫ √ = (∫ βˆ’ 𝑑𝑒 βˆšπ‘’ √ ) βˆ’ (∫ 𝑑π‘₯) βˆ’ (∫ 1 √1 βˆ’ π‘₯ = (∫ βˆ’π‘’ 𝑑π‘₯ = ∫ ( ) 𝑒 =1βˆ’π‘₯ 𝑑𝑒 = βˆ’2π‘₯𝑑π‘₯ 𝑑π‘₯) 𝑑𝑒) βˆ’ (∫ 1 𝑑π‘₯) √1 βˆ’ π‘₯ π‘₯ + 𝐢 = βˆ’2√1 βˆ’ π‘₯ βˆ’ sin = βˆ’2𝑒 βˆ’ sin 4.

∫ 𝑑π‘₯ = ∫ ( 1 1 𝑒 βˆ’ 𝑒 +𝐢 7 9 1 1 sin π‘₯ βˆ’ sin π‘₯ + 𝐢 7 9 )( ) 𝑑π‘₯ = ∫ ( + ) 𝑑π‘₯ 10 𝐴 𝐡 = + β†’ 10 = 𝐴(π‘₯ + 2) + 𝐡(π‘₯ βˆ’ 3) (π‘₯ βˆ’ 3)(π‘₯ + 2) π‘₯ βˆ’ 3 π‘₯ + 2 There are a few different ways of finding 𝐴 and 𝐡. One way: Plug in 3 for π‘₯: 10 = 𝐴(5) + 𝐡(0) β†’ 𝐴 = 2 Plug in -2 for π‘₯: 10 = 𝐴(0) + 𝐡(βˆ’5) β†’ 𝐡 = βˆ’2 So we get: ∫ ( βˆ’ ) 𝑑π‘₯ = 2 ln|π‘₯ βˆ’ 3| βˆ’ 2 ln|π‘₯ + 2| + 𝐢 (You could also do this one by completing the square. ∫(sin π‘₯ cos π‘₯ )𝑑π‘₯ 𝑒 = sin π‘₯ .5.) . 𝑑𝑒 = (cos π‘₯ )𝑑π‘₯ ∫(sin π‘₯ cos π‘₯ )(cos π‘₯ )𝑑π‘₯ = ∫(sin π‘₯ )(1 βˆ’ sin π‘₯ )(cos π‘₯ )𝑑π‘₯ = ∫ 𝑒 (1 βˆ’ 𝑒 )𝑑𝑒 = ∫(𝑒 βˆ’ 𝑒 )𝑑𝑒 = = 6.

∫ ( ∫ ) 3 3 ) 𝑑𝑒 = 𝑒 βˆ’ 3𝑒 + 3 ln|𝑒 + 1| + 𝐢 𝑒+1 2 3 π‘₯ βˆ’ 3π‘₯ + 3 ln |π‘₯ + 1| + 𝐢 2 𝑑π‘₯ 1 (4 tan πœƒ + 4) π‘₯ = 2 tan πœƒ . 𝑑π‘₯ = 2 sec πœƒ π‘‘πœƒ 1 2 sec πœƒπ‘‘πœƒ (4 sec πœƒ ) 1 1 1 =∫ 2 sec πœƒπ‘‘πœƒ = ∫ π‘‘πœƒ 8 sec πœƒ 4 sec πœƒ 1 1 1 π‘₯ = ∫ cos πœƒ π‘‘πœƒ = sin πœƒ + 𝐢 = ( )+𝐢 4 4 4 √π‘₯ + 4 2 sec πœƒπ‘‘πœƒ = ∫ The last equality comes from a reference triangle: .7. ∫ √ 𝑑π‘₯ A rationalizing substitution is the way to go: 𝑒 = √π‘₯ . ∫ (3𝑒 βˆ’ 3 + = 8. 𝑑π‘₯ = 3𝑒 𝑑𝑒 β‹… 3𝑒 𝑑𝑒 ∫ Now use long division. π‘₯ = 𝑒 .

∫(π‘₯ sin π‘₯ )𝑑π‘₯ = βˆ’π‘₯ cos π‘₯ + 3π‘₯ sin π‘₯ + 6π‘₯ cos π‘₯ βˆ’ 6 sin π‘₯ + 𝐢 10. 𝑑𝑒 = sec π‘₯ tan π‘₯ 𝑑π‘₯ ∫(tan π‘₯ sec π‘₯ )(sec π‘₯ tan π‘₯ )𝑑π‘₯ = ∫(sec π‘₯ βˆ’ 1)(sec π‘₯ )(sec π‘₯ tan π‘₯ )𝑑π‘₯ = ∫(𝑒 βˆ’ 1)𝑒 𝑑𝑒 = ∫(𝑒 βˆ’ 𝑒 )𝑑𝑒 = 1 1 1 1 𝑒 βˆ’ 𝑒 + 𝐢 = sec π‘₯ βˆ’ sec π‘₯ + 𝐢 5 3 5 3 . ∫(tan π‘₯ sec π‘₯ )𝑑π‘₯ 𝑒 = sec π‘₯ . or save yourself some writing and use the tic-tac-toe method.9. ∫(π‘₯ sin π‘₯ )𝑑π‘₯ You can integrate by parts multiple times.

the original integral must diverge. 𝑑π‘₯ = (3 sec πœƒ tan πœƒ )π‘‘πœƒ 𝑑π‘₯ . ∫ 𝑑π‘₯ = ∫ 𝑑π‘₯ + ∫ 𝑑π‘₯ You can check either of these integrals first. ∫ √ π‘₯ = 3 sec πœƒ . You MUST split up the integral at the infinite discontinuity.11. Say you check the second one: 𝑑π‘₯ = lim ∫ lim β†’ *βˆ’ √ β†’ ∫ π‘₯ + = lim β†’ 𝑑π‘₯ = lim *βˆ’ √ + √ β†’ *βˆ’3π‘₯ + = +=∞ Since this integral diverges. π‘₯ = 0. WARNING: DO NOT rewrite the original integral as *βˆ’3π‘₯ + and solve it from there. . π‘₯ > 3 √9 sec πœƒ βˆ’ 9 (3 sec πœƒ tan πœƒ )π‘‘πœƒ ∫ 3 sec πœƒ = ∫ (√9 sec πœƒ βˆ’ 9) (tan πœƒ )π‘‘πœƒ = ∫ (√9 tan πœƒ) (tan πœƒ )π‘‘πœƒ = ∫(3 tan πœƒ)(tan πœƒ )π‘‘πœƒ = 3 ∫(tan πœƒ )π‘‘πœƒ = 3 ∫(sec πœƒ βˆ’ 1)π‘‘πœƒ √π‘₯ βˆ’ 9 = 3(tan πœƒ βˆ’ πœƒ ) + 𝐢 = 3 ( βˆ’ sec 3 π‘₯ )+𝐢 3 The last equality comes from a reference triangle. 12. there’s no need to check the other one.

13. ∫(cos 7π‘₯ β‹… sin 4π‘₯ )𝑑π‘₯ Make use of the following identity: 1 sin(π‘šπ‘₯ ) cos(𝑛π‘₯ ) = [sin(π‘š βˆ’ 𝑛)π‘₯ + sin(π‘š + 𝑛)π‘₯ ] 2 1 1 ∫ [sin(βˆ’3π‘₯ ) + sin(11π‘₯)]𝑑π‘₯ = ∫[βˆ’sin(3π‘₯ ) + sin(11π‘₯)]𝑑π‘₯ 2 2 1 1 1 = ( cos(3π‘₯ ) βˆ’ cos(11π‘₯ )) + 𝐢 2 3 11 14. ) 𝑑π‘₯ = π‘₯ + ∫ ( ) 𝑑π‘₯ 𝑒 =π‘₯ +π‘₯+1 𝑑𝑒 = (2π‘₯ + 1)𝑑π‘₯ 𝑑𝑒 = π‘₯ + ln |𝑒| + 𝐢 = π‘₯ + ln|π‘₯ + π‘₯ + 1| + 𝐢 𝑒 . ∫ ∫ (1 + =π‘₯+∫ 𝑑π‘₯ Do long division of polynomials first.

∫ =∫ 8π‘₯ βˆ’ π‘₯ = βˆ’(π‘₯ βˆ’ 8π‘₯ ) = βˆ’(π‘₯ βˆ’ 8π‘₯ + 16) + 16 = βˆ’(π‘₯ βˆ’ 4) + 16 √ √ ( =∫ 16. 𝐢 = 3 ∫ 2 3 𝑑π‘₯ + ∫ 𝑑π‘₯ = 2 ln |π‘₯ + 1| + 3 tan π‘₯+1 π‘₯ +1 π‘₯+𝐢 . ∫ 𝑒 = π‘₯ βˆ’ 4.15. 𝑑𝑒 = 𝑑π‘₯ ) 𝑑𝑒 √16 βˆ’ 𝑒 𝑒 ( ) + 𝐢 = sin 4 = sin 𝑑π‘₯ = ∫ ( )( ) 𝑑π‘₯ = ∫ ( π‘₯βˆ’4 )+𝐢 4 𝑑π‘₯ + ∫ 𝑑π‘₯ 2π‘₯ + 3π‘₯ + 5 𝐴 𝐡π‘₯ + 𝐢 = + (π‘₯ + 1)(π‘₯ + 1) π‘₯ + 1 π‘₯ + 1 2π‘₯ + 3π‘₯ + 5 = 𝐴(π‘₯ + 1) + (𝐡π‘₯ + 𝐢 )(π‘₯ + 1) π‘₯ = βˆ’1: 2 βˆ’ 3 + 5 = 𝐴(2) + 0 4 = 2𝐴 β†’ 𝐴 = 2 2π‘₯ + 3π‘₯ + 5 = 2(π‘₯ + 1) + (𝐡π‘₯ + 𝐢 )(π‘₯ + 1) 2π‘₯ + 3π‘₯ + 5 = 2π‘₯ + 2 + (𝐡π‘₯ + 𝐢 )(π‘₯ + 1) 3π‘₯ + 3 = (𝐡π‘₯ + 𝐢 )(π‘₯ + 1) 3 = 𝐡π‘₯ + 𝐢 𝐡 = 0.

𝑣 = π‘₯ 1 1 1 1 1 = π‘₯ ln π‘₯ βˆ’ ∫ ( π‘₯ ) ( 𝑑π‘₯) = π‘₯ ln π‘₯ βˆ’ ∫ π‘₯ 𝑑π‘₯ 3 3 π‘₯ 3 3 1 1 = π‘₯ ln π‘₯ βˆ’ π‘₯ + 𝐢 3 9 . 𝑑𝑣 = π‘₯ 𝑑π‘₯ 𝑑𝑒 = 𝑑π‘₯.17. ∫(π‘₯ ln π‘₯ )𝑑π‘₯ β†’ ∫ 𝑒 1 + 𝑒 5 𝑑π‘₯ = lim β†’ 1 ]=0+ 𝑒 5 *βˆ’ 𝑒 = + 1 5𝑒 𝑒 = ln π‘₯ . ∫ 𝑒 𝑑π‘₯ = lim 1 = lim [βˆ’ 𝑒 β†’ 5 18.

You need to do that because. for values of π‘₯ between and .19. 20. sin 3π‘₯ is NEGATIVE. ∫ √1 βˆ’ cos 6π‘₯ 𝑑π‘₯ = ∫ =∫ √2 sin 3π‘₯ 𝑑π‘₯ = ∫ =∫ √1 βˆ’ (1 βˆ’ 2 sin 3π‘₯ )𝑑π‘₯ √2 β‹… |sin 3π‘₯ |𝑑π‘₯ √2 βˆ’βˆš2 sin 3π‘₯ 𝑑π‘₯ = * cos 3π‘₯+ 3 2√2 √2 √2 √2 √2 = ( cos 2πœ‹) βˆ’ ( cos πœ‹) = βˆ’ (βˆ’ ) = 3 3 3 3 3 Note that I included a negative sign once I removed the absolute value bars. 𝑑𝑒 = π‘₯ cos πœƒ π‘‘πœƒ ∫ √25 βˆ’ 25 sin πœƒ β‹… 5 cos πœƒ π‘‘πœƒ = ∫ √25 cos πœƒ β‹… 5 cos πœƒ π‘‘πœƒ = ∫ 5 cos πœƒ β‹… 5 cos πœƒ π‘‘πœƒ = 25 ∫ cos πœƒ π‘‘πœƒ 1 25 1 = 25 ∫ (1 + cos 2πœƒ )π‘‘πœƒ = [πœƒ + sin 2πœƒ] 2 2 2 25 [πœƒ + sin πœƒ cos πœƒ ] + 𝐢 = 2 25 π‘₯ π‘₯ √25 βˆ’ π‘₯ = *sin + β‹… ++𝐢 2 5 5 5 The last equality comes from a reference triangle. . ∫ √25 βˆ’ π‘₯ 𝑑π‘₯ π‘₯ = 5 sin πœƒ .

Extra Credit: Evaluate ∫(𝐢𝐸𝑁𝑆𝑂𝑅𝐸𝐷 )𝑑π‘₯. .

1 π‘₯ ( )+𝐢 π‘Ž βˆšπ‘Ž βˆ’ π‘₯ 1 1 π‘₯ ∫ 𝑑π‘₯ = ( ) tan ( ) + 𝐢 π‘Ž +π‘₯ π‘Ž π‘Ž 1 1 π‘₯ ∫ 𝑑π‘₯ = ( ) sec | | + 𝐢 π‘Ž π‘Ž π‘₯√π‘₯ βˆ’ π‘Ž ∫ ∫ 𝑑π‘₯ = sin 1 𝑑π‘₯ = sinh π‘₯ ( )+𝐢 π‘Ž βˆšπ‘Ž + π‘₯ 1 π‘₯ ∫ 𝑑π‘₯ = cosh ( ) + 𝐢 (π‘₯ > π‘Ž) π‘Ž √π‘₯ βˆ’ π‘Ž 1 π‘₯ tanh ( ) + 𝐢.For all of these formulas. π‘₯ < π‘Ž 1 π‘Ž π‘Ž ∫ 𝑑π‘₯ = { 1 π‘₯ π‘Ž βˆ’π‘₯ coth ( ) + 𝐢. π‘Ž must be a positive constant. π‘₯ > π‘Ž π‘Ž π‘Ž 1 1 π‘₯ ∫ 𝑑π‘₯ = βˆ’ sech ( ) + 𝐢 (π‘Ž > π‘₯ > 0) π‘Ž π‘Ž π‘₯βˆšπ‘Ž βˆ’ π‘₯ 1 1 π‘₯ ∫ 𝑑π‘₯ = βˆ’ csch | | + 𝐢 π‘Ž π‘Ž π‘₯βˆšπ‘Ž + π‘₯ ∫(sec π‘Žπ‘₯ )𝑑π‘₯ = ( ) + ∫(sec π‘Žπ‘₯ )𝑑π‘₯ (𝑛 β‰  1) 1 [cos(π‘š βˆ’ 𝑛)π‘₯ βˆ’ cos(π‘š + 𝑛)π‘₯ ] 2 1 sin(π‘šπ‘₯ ) cos(𝑛π‘₯ ) = [sin(π‘š βˆ’ 𝑛)π‘₯ + sin(π‘š + 𝑛)π‘₯ ] 2 1 cos(π‘šπ‘₯) cos(𝑛π‘₯) = [cos(π‘š βˆ’ 𝑛)π‘₯ + cos(π‘š + 𝑛) π‘₯ ] 2 sin(π‘šπ‘₯ ) sin(𝑛π‘₯ ) = .